1959
DOI: 10.1037/h0048521
|View full text |Cite
|
Sign up to set email alerts
|

Group versus individual problem-solving.

Abstract: Is THE performance of a group superior to the performance of an individual? Studies by Shaw (1932), Watson (1928), andTaylor andFaust (1952) have found that group performance is significantly superior. In the Taylor-Faust study (1952), for example, groups composed of two and four members were found to solve more Twenty Questions problems in fewer questions and in shorter time than did persons working individually.These studies have based their statistical analysis upon the null hypothesis that no difference ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 9 publications
1
27
0
2
Order By: Relevance
“…Examples include object transfer problems (e.g., Shaw, 1932), water jar or gold dust problems (e.g., Davis & Fistle, 1963), anagrams (e.g., Faust, 1959), and most of the tasks in the group problem solving traditions summarized by Kelley & Thibaut (1969), Hackman and Morris (1975), Hastie (1986), Hill (1982, Lorge, Fox, Davitz, andBrenner (1958), andMcGrath (1984).…”
Section: Collective Inductionmentioning
confidence: 99%
“…Examples include object transfer problems (e.g., Shaw, 1932), water jar or gold dust problems (e.g., Davis & Fistle, 1963), anagrams (e.g., Faust, 1959), and most of the tasks in the group problem solving traditions summarized by Kelley & Thibaut (1969), Hackman and Morris (1975), Hastie (1986), Hill (1982, Lorge, Fox, Davitz, andBrenner (1958), andMcGrath (1984).…”
Section: Collective Inductionmentioning
confidence: 99%
“…It has been said that the greater a person ts knowl e_dge of a. subject, the 1 ess conformant he or she will be, so perhaps it can be said that the inverse is also true~-the less a personts knowl~dge on a subject, the more conformant he or she will become. This idea is· reinforced by another study which es tab 1 i shed the fact that conformity is increased with i ncre'ased contra l by the agent of conformity (Fearing and Krise 1941). This conformity is self-perpetuating: a study by Scott (1956) showed that the greater the number of members in a_ group who hold a value and the more strongly they hold it, the more important it becomes to all.…”
Section: · Group Identitymentioning
confidence: 78%
“…Faust (1958) identified complex sentence anagram tasks as "multiple-step" tasks, as compared to the "single-step" needed to solve one-word ("Eureka") problems. Groups have been found to perform better at complex tasks, while individuals performed better at the less-structured, single-step tasks (Faust, 1958, p. 17;Lord 1976, p. 87).…”
Section: Subject Populationmentioning
confidence: 99%
“…Methodological defects exempted experiments 9 and 10 as the methods for recording responses were different: nominal groups wrote while real groups tape-recorded oral responses. Also exempted was experiment 8 (Faust, 1958) because of the use of complex tasks which required a multiple-step development as compared to the simple single-step responses called for in the other brainstorming studies. After performance percentages were computed for the remaining set of studies (Table 1) Meta-Analysis Rejuvenates.…”
Section: The Size Of Groupsmentioning
confidence: 99%